Hope and insufficiency : capacity building in ethnographic comparison - Douglas-Jones, Rachel; Shaffner, Justin (Berghahn Books, 2021)
A process through which skills, knowledge, and resources are expanded, capacity building, remains a tantalizing and pervasive concept throughout the field of anthropology, though it has received little in the way of critical analysis. By exploring the concept's role in a variety of different settings including government lexicons, religious organizations, environmental campaigns, biomedical training, and fieldwork from around the globe, Hope and Insufficiency seeks to question the histories, assumptions, intentions, and enactments that have led to the ubiquity of capacity building, thereby developing a much-needed critical purchase on its persuasive power.